If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(2y + 7) = -18 Reorder the terms: -2(7 + 2y) = -18 (7 * -2 + 2y * -2) = -18 (-14 + -4y) = -18 Solving -14 + -4y = -18 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + -4y = -18 + 14 Combine like terms: -14 + 14 = 0 0 + -4y = -18 + 14 -4y = -18 + 14 Combine like terms: -18 + 14 = -4 -4y = -4 Divide each side by '-4'. y = 1 Simplifying y = 1
| 7=0.166666667s+11 | | 1+x=2x+3 | | 4=6+5v-6v | | -3x-5=25+7x | | 7y=80+9y | | 4m+8=9m-7 | | 7-2(5-x)=5x-2(x-1) | | 7ac-8b+7c= | | m^2-6m-55=0 | | 9x^2+16x-8=0 | | x+2x=7,5 | | 33=(5+2w)w | | 12=3x+4 | | 0.25x=-2 | | 4=5x+10 | | 0.166666667s=4 | | 0=2w^2+5w-33 | | 6y-14=5y-3 | | 3x^3+15X^2+18=0 | | 4t^2+2t=0 | | -s=83 | | solver-9.8=-5.8 | | -5y-11=-4y | | -4z=28 | | 6x^2+x-1= | | 5k^2+3k-2=0 | | 8-9x=-8x | | 5x+(3x+2)=106 | | 0.25x=8 | | 4c+3=11 | | 5x^2+45x= | | T^2+6t-9=0 |